Step-by-step explanation:
=9x+2(2x+3)
=9x+4x+6
=13x+6 I hope so,
Answer:
The answer is Zero
Step-by-step explanation:
P+6/6+m*n
-6+6/6+4(-1)
0/-2
The answer is Zero
Answer:
Step-by-step explanation:
2g + h = 2 --------------(I)
g - h = -5------------(II)
g = -5 + h
Plugin g = -5 + h in equation (I)
2(-5 + h) + h = 2 {Distributive property:a(b+c) = a*b +a*c}
(-5)*2 + h *2 + h= 2
-10 + 2h + h = 2
3h = 2 + 10
3h = 12
h = 12/3
h = 4
Substitute h= 6 in equation (I)
2g + 4 = 2
2g = 2 - 4
2g = -2
g = -2/2
g = -1
Answer:
to get our answer, we multiply the two fractions together. 6/8× 3/5= 3/5 or 0.6
hope this helps! mark me brailyest please :D